Exploration of novel inhibitors of mycobacterium tuberculosis dihydrofolate reductase for tuberculosis treatment - Mollo Palomino, Kelly Cristina (2024)
Tuberculosis is a lethal illness caused by Mycobacterium tuberculosis, considered, to date, the second global cause of death. Despite this fact, the treatment still relies on 40-year-old paradigms, and with the rise of resistant tuberculosis cases and complications due to HIV coinfection, the need for new anti-tuberculosis agents becomes urgent. An attractive target to consider for designing new drugs to fight tuberculosis is the enzyme Mycobacterium tuberculosis dihydrofolate reductase (MtbDHFR), key macromolecule in the folate pathway whose inhibition would arrest DNA synthesis in the bacteria and lead to its death. This thesis explores the molecular scaffolds reported during the last decade as virtual and in vitro inhibitors of MtbDHFR that could be used as leads for further development. Also, it covers the state of the art of MtbDHFR, in comparison with its human counterpart and the strategies used in the discovery of the selected inhibitors.